Antimigratory Effects of the Methanol Extract from Momordica charantia on Human Lung Adenocarcinoma CL1 Cells - Hsu, Hsue-Yin (Hindawi Publishing Corporation, 2012)
Momordica charantia has been found to exhibit anticancer activity, in addition to its well-known therapeutic functions. We have demonstrated that the leaf extract of Momordica charantia (MCME) induces apoptosis in several human cancer cells through caspase- and mitochondria-dependent pathways. In this study, a different susceptibility to MCME was found in human lung adenocarcinoma CL1 cells with different metastatic ability, leading to the significant difference of cell viability and invasiveness between MCME-treated CL1-0 and CL1-5 cells. MCME was found to upregulate the expression of Wnt-2 and affect the migratory and invasive ability of CL1 cells through suppressed MMP-2 and MMP-9 enzymatic activities. We proposed that MCME mediates inhibition against migration of CL1 cells by reducing the expression and activation of Src and FAK to decrease the expression of downstream Akt, β-catenin, and MMPs.